New multi-target based therapeutics against an opportunistic superbug - Premkumar, Jayaraman. (2013)
Pseudomonas aeruginosa (P. aeruginosa) is one of the most opportunistic and challenging Gram-negative pathogens, often resistant to a number of widely used antibiotics even when combination therapies are administered, thereby joining the ranks of “superbugs”. Hence, there is a dearth of treatment options for community-acquired and nosocomial Pseudomonas infections due to several rapidly emerging multidrug-resistant phenotypes along with the complexity of rising resistance rates. Taken together, it is imperative to discover more potent drugs and novel therapeutic strategies to combat the infections caused by this superbug. It is recently highly appreciated that instead of inhibition of an individual target in the disease-associated network, modulating activity of multiple targets may be required to achieve optimal therapeutic benefit against robust pathogens. Multi-target therapeutics can be developed by two distinct approaches, a combination of two or more different agents to inhibit dissimilar targets or designing a multi-target specific single hybrid entity. The research presented here utilized both combinations based searches and designing hybrid compounds with pre-defined promiscuity methods for the discovery of novel therapeutics against the study pathogen.